A survey on joint optimization of MEC caching and transcoding for video streaming - Jia LI; Renchao XIE; Qingmin JIA; Tao HUANG; Yunjie LIU; Li SUN (Dianxin kexue)
To deal with the huge challenges in futuremobile networks,the industry has proposed adaptive bit rate(ABR)technology andmobile edge computing(MEC),aiming to provide users with diverse services of high quality of experience,low latency and high bandwidth.Combining ABR and MEC to optimize the distribution of video content has been quite important for improving network performance and quality of experience.Especially,the joint optimization of network resources has arisen as an essential research topic.An overview of MEC was firstly given,and then the existing work in the industry on the joint optimization problem of MEC caching and transcoding oriented to adaptive streaming was analyzed and compared.Finally,the existing challenges in the future were summarized.